Estratégias de planejamento de Smart Grids: uma abordagem baseada em meta-heurísticas e simulação - SANTOS, Ederson Costa dos (Universidade Federal do Pará, 2017)
Currently, the Electric Power System undergoes major modifications, which focus on various levels and sub-levels of the generation, transmission and distribution subsystems, all of which are based on Smart Grids logic. This concept is characterized by the inclusion of new digital technologies in the electrical system, with the purpose of bringing security, speed, monitoring, among many other benefits. For the full development of Smart Grids, a lot still needs to be done in several areas of research. In this line, this work presents simulations of a Smart Grid planning model, characterizing it from protocols, which are trends for this type of network. For this, we also analyzed an optimization method, which uses intelligent algorithms to optimize devices in a Smart Grid. The proposed solution is based on the optimized allocation of equipment in acommunication network, which uses as its physical transmission medium its own electrical wiring, Power Line Communitation technology. In this network are inserted Smart Grid applications defined through IEC 61850. Thus, with this proposed model, simulations were performed in the Network Simulator-3 discrete event software. The results show a significant decrease in the quantity of equipment, maintaining the quality levels to the applications.